Examination of the Life Expectancy of Patients with Burns over 20% of Their Total Body Surface Area in Comparison to the Rest of the Population. Issue 6 (November 2017) - Weissman, Oren; Wagman, Yonatan; Givon, Adi; Radomislensky, Irina; Peleg, Kobi; Stavrou, Demetris; Haik, Josef; Tessone, Ariel
Abstract : Patients with extensive burn injuries suffer from multisystem trauma, which affects their medical, psychological, and social well-being for many years. Monitoring those patients has revealed changes in the endocrine, cardiac, and respiratory systems years after the injury. Our study tries to examine whether changes manifest as a higher risk of death during their lifespan, compared with the general population. Data from the years 1998 to 2013 regarding two groups of patients was obtained from a national trauma registry: one group had suffered burns over 20% of their TBSA and survived the hospitalization period and the second group was a control group of patients admitted with minimal trauma (Injury Severity Score = 1—minor injury to a single body region). Mortality rates during the posthospitalization period were compared after adjusting for age and follow-up periods. The authors collected 1115 second- or third-degree burn victims with 20% TBSA and 81, 688 trauma victims with an Injury Severity Score = 1. Follow-up periods ranged from 8 months to almost 17 years. When comparing the groups after correcting for age, sex, and follow-up period, no significant differences in mortality risk were found. Possible explanations for the lack of differences in mortality risk include the lack of an adequate follow-up period, a misguided research hypothesis (ie, despite existence of physiological changes in burn patients, these changes do not affect the lifespan), or a control group that does not optimally represent mortality in the general population.